Lactobacillus fermentum HFY06 reduced CCl4-induced hepatic damage in Kunming mice. Issue 1 (20th December 2019) - Li, Fang; Lu, De-Yun; Zhong, Qiu; Tan, Fang; Li, Wenfeng; Liao, Wei; Zhao, Xin
Abstract : This study was conducted to investigate the preventative effect of Lactobacillus fermentum HFY06 on carbon tetrachloride (CCl4 )-induced liver injury in Kunming mice. Abstract : This study was conducted to investigate the preventative effect of Lactobacillus fermentum HFY06 on carbon tetrachloride (CCl4 )-induced liver injury in Kunming mice. Mice were treated with HFY06, then liver damage was induced using CCl4 . Evaluation indicators included the activities of aspartate aminotransferase (AST), triglycerides (TG), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and malondialdehyde (MDA) in serum; cytokines levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) in serum; and related gene expressions of nuclear factor-κB (NF-κB), TNF-α, cyclooxygenase-2 (COX-2), copper/zinc superoxide dismutase (Cu/Zn-SOD), manganese superoxide dismutase (Mn-SOD), and catalase (CAT). Liver tissue was stained with hematoxylin and eosin for pathological analysis. Compared with the model group, HFY06 reduced the liver index, increased the serum SOD and GSH-Px activities, and reduced the AST, TG, and MDA activities in the mice. Inflammation-related IL-6, TNF-α and IFN-γ levels were also reduced after treatment with a high dose of HFY06. Pathological observation showed that CCl4 damaged the mouse livers, which were significantly improved after treatment with silymarin and HFY06. qPCR also confirmed that the high dose of HFY06 (10 9 colony-forming units [CFU] per kg per day) upregulated the mRNA expression of the antioxidant genes, Cu/Zn-SOD, Mn-SOD, and CAT, in the liver tissue and downregulated the mRNA expression of the inflammatory factors, NF-κB, TNF-α and COX-2, but HFY06 was less effective than silymarin. These findings indicate that HFY06 prevented CCl4 -induced liver damage in vivo but was less effective than silymarin. Thus, HFY06 may have a potential role in treating liver diseases.